Gender Equality from the Police Recruits’ Perspective: Does Their Gender Make the Difference? Iva Balgač, Irena Cajner Mraović, Krunoslav Borovec (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
United Nations’ Sustainable Development Goals 5 and 16 focus on gender equality, peace, justice, and strong institutions. One of these institutions is the police. Police work includes many opportunities to protect and promote gender equality. This study aims to find whether differences in attitudes towards gender equality between male and female police recruits before and after basic police training exist. The results reveal that the difference between male and female recruits is statistically significant both at the beginning and at the end of their basic police education. A statistically significant difference concerning the gender of the recruit was determined concerning the combination of three dependent variables that measured attitudes about gender equality, as well as about each individual variable. Furthermore, the research found that the influence of gender on differences in attitudes towards gender equality was stronger after education than before education for the police profession.